ANALISIS LAPORAN PERTANGGUNGJAWABAN DANA BANTUAN SEKOLAH (BOS) PADA SEKOLAH MENENGAH ATAS NEGERI 1 KEUMALA KABUPATEN PIDIE - Fariz Refzal; Emi Suryani; Fitri Yunina (BE-HISZ : Journal of Economics and Accounting, 2024)
The aim of this research is to analyze the Accountability Report for School Assistance Funds (BOS) at State Senior High School (SMA) 1 Keumala, Pidie Regency. The method that will be used in this research is the descriptive analysis method, which is a type of research that aims to provide a systematic, factual and accurate description of the data in the field which is focused on High School Operational Assistance (BOS) funds at SMA Negeri 1 Keumala, Pidie Regency. . The object of the research is the High School Operational Assistance (BOS) funds at SMA Negeri 1 Keumala Kab. Pidie. To obtain data and information for writing this thesis, research was carried out directly at SMA Negeri 1 Keumala Kab. Pidie whose address is Jalan Beureunuen – Tangse KM. 12, Keumala District, Pidie Regency, Aceh   The results of the research show that the planning for High School Operational Assistance (BOS) funds at SMA Negeri 1 Keumala, Pidie Regency increased in 2016, namely IDR 422,450,000 and there was a decrease in BOS funds amounting to IDR 388,640,000 in 2017. Implementation of Operational Assistance funds High School (BOS) at SMA Negeri 1 Keumala Kab. Pidie 2015 to 2017 was implemented well. The use of BOS funds has a very important (urgent) influence on student learning outcomes and improving school quality, this is reflected in increasing academic achievement scores and non-academic achievements. Supervision of the management of BOS SMA funds from 2015 to 2017 was carried out by internal and external parties and reporting included planning, implementation, monitoring and evaluation of operational assistance funds for senior high schools.